Ionization balance of impurities in turbulent scrape-off layer plasmas I: local ionization-recombination equilibrium. (3rd November 2015) - Guzman, F; Marandet, Y; Tamain, P; Bufferand, H; Ciraolo, G; Ghendrih, Ph; Guirlet, R; Rosato, J; Valentinuzzi, M
Abstract: In magnetized fusion devices, cross field impurity transport is often dominated by turbulence, in particular in the scrape-off layer. In these outer regions of the plasma, fluctuations of plasma parameters can be comparable to mean values, and the way ionization and recombination sources are treated in transport codes becomes questionnable. In fact, sources are calculated using the mean density and temperature values, with no account of fluctuations. In this work we investigate the modeling uncertainties introduced by this approximation, both qualitatively and quantitatively for the local ionization equilibrium. As a first step transport effects are neglected, and their role will be discussed in a companion paper. We show that temperature fluctuations shift the ionization balance towards lower temperatures, essentially because of the very steep temperature dependence of the ionization rate coefficients near the threshold. To reach this conclusion, a thorough analysis of the time scales involved is carried out, in order to devise a proper way of averaging over fluctuations. The effects are found to be substantial only for fairly large relative fluctuation levels for temperature, that is of the order of a few tens of percents.